Estimated losses of plant biodiversity in the United States from historical N deposition (1985–2010). Issue 7 (1st July 2013) - Clark, Christopher M.; Morefield, Philip E.; Gilliam, Frank S.; Pardo, Linda H.
Abstract : Although nitrogen (N) deposition is a significant threat to herbaceous plant biodiversity worldwide, it is not a new stressor for many developed regions. Only recently has it become possible to estimate historical impacts nationally for the United States. We used 26 years (1985–2010) of deposition data, with ecosystem‐specific functional responses from local field experiments and a national critical loads (CL) database, to generate scenario‐based estimates of herbaceous species loss. Here we show that, in scenarios using the low end of the CL range, N deposition exceeded critical loads over 0.38, 6.5, 13.1, 88.6, and 222.1 million ha for the Mediterranean California, North American Desert, Northwestern Forested Mountains, Great Plains, and Eastern Forest ecoregions, respectively, with corresponding species losses ranging from <1% to 30%. When we ran scenarios assuming ecosystems were less sensitive (using a common CL of 10 kg·ha −1 ·yr −1, and the high end of the CL range) minimal losses were estimated. The large range in projected impacts among scenarios implies uncertainty as to whether current critical loads provide protection to terrestrial plant biodiversity nationally and urge greater research in refining critical loads for U.S. ecosystems.